Flux Synthesis of A‐site Disordered Perovskite La0.5M0.5TiO3 (M═Li, Na, K) Nanorods Tailored for Solid Composite Electrolytes - Tao Wang; Jiyoung Ock; X. Chelsea Chen; Fan Wang; Meijia Li; Matthew S. Chambers; Gabriel M. Veith; Lauren B. Shepard; Susan B. Sinnott; Albina Borisevich; Miaofang Chi; Amit Bhattacharya; et al. (Advanced Science)
Abstract Inorganic fillers play an important role in improving the ionic conductivity of solid composite electrolytes (SCEs) for Li‐ion batteries. Among inorganic fillers, perovskite‐type lithium lanthanum titanate (LLTO) stands out for its high bulk Li+ conductivity on the order of 10−3 S cm−1 at room temperature. According to a literature survey, the optimal LLTO filler should possess the following characteristics: i) a single‐crystal structure to minimize grain boundaries; ii) a small particle size to increase the filler/polymer interface area; iii) a 1D morphology for efficient interface channels; and iv) cubic symmetry to facilitate rapid bulk Li+ diffusion within the filler. However, the synthesis of single crystal, 1D LLTO nanomaterials with cubic symmetry is challenging. Herein, a flux strategy is developed to synthesize La0.5M0.5TiO3 (LMTO, M═Li, Na, and K) single‐crystal nanorods with an A‐site‐disordered, cubic perovskite phase. The flux media promotes the oriented growth of nanorods, prevents nanorods from sintering, and provides multiple alkali metal ion doping at M sites to stabilize the cubic phase. SCEs compositing the Li+‐conducting LMTO nanorods as fillers and poly[vinylene carbonate‐co‐lithium sulfonyl(trifluoromethane sulfonyl)imide methacrylate] matrix exhibit more than twice the conductivity of the neat polymer electrolyte (30.6 vs 14.0 µS cm−1 at 303 K).